A monitoring and evaluation framework on capacity-strengthening for gender-and youth-responsive research: A user guide - Iradukunda, Francois; Cole, Steven Michael; Mangheni, Margaret Najjingo; Asiimwe, Elizabeth (CGIAR Initiative on Excellence in Agronomy, 2024)
The Monitoring and Evaluation (M&E) framework for gender- and youth-responsive research in agronomy addresses the critical need for gender and social inclusion skills among agricultural researchers. Despite numerous capacity-strengthening interventions since the Beijing Platform for Action in 1995, their effectiveness remains under-evaluated. This framework, developed under CGIAR’s Excellence in Agronomy (EiA) Research Initiative, aims to generate evidence on the impact of training programs designed to enhance gender- and youth-related research capacities. It includes a comprehensive approach encompassing training needs assessment, process evaluation, and post-training follow-up, applicable to both in-presence and virtual training models. The framework was initially implemented in collaboration with the GREAT program at Makerere University, Uganda, and tailored to EiA’s workflow. It provides a structured methodology to evaluate gender/youth training effectiveness, ensuring that acquired skills are successfully applied in research settings to promote gender and generational equality in agricultural research and development.